2005
DOI: 10.1525/aa.2005.107.4.575
|View full text |Cite
|
Sign up to set email alerts
|

Between Religion and Desire: Being Muslim and Gay in Indonesia

Abstract: Thousands of Indonesian men now identify as both “gay” and “Muslim.” How do these men understand the relationship between religion and sexuality? How do these understandings reflect the fact that they live in the nation that is home to more Muslims than any other? In this article, I address questions such as these through an ethnographic study of gay Muslims. I argue that dominant social norms render being gay and being Muslim “ungrammatical” with each other in the public sphere that is crucial to Muslim life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
73
0
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(77 citation statements)
references
References 21 publications
1
73
0
3
Order By: Relevance
“…I present six cases to illustrate different ways of being sexual vis-à-vis the discourse of morality among young people in contemporary Indonesia. This contribution extends previous studies that have mainly been conducted among Indonesian Muslims (Bennett, 2007;Boellstorff, 2005; S.G. Davies, 2011;Kailani, 2012;Parker, 2009;Smith-Hefner, 2005;2006;van Wichelen, 2010), by exploring the interplay between religion, morality and sexual subjectivity in the context of young Indonesian Christians (i.e. Catholics and Protestants).…”
Section: Introductionsupporting
confidence: 74%
“…I present six cases to illustrate different ways of being sexual vis-à-vis the discourse of morality among young people in contemporary Indonesia. This contribution extends previous studies that have mainly been conducted among Indonesian Muslims (Bennett, 2007;Boellstorff, 2005; S.G. Davies, 2011;Kailani, 2012;Parker, 2009;Smith-Hefner, 2005;2006;van Wichelen, 2010), by exploring the interplay between religion, morality and sexual subjectivity in the context of young Indonesian Christians (i.e. Catholics and Protestants).…”
Section: Introductionsupporting
confidence: 74%
“…Halstead and Lewicka described how homosexuality in Islamic cultures is largely devoid of the politicization that forms the basis of the Western gay movement and, thus, the notion of a gay identity does not exist for Muslims outside of Western cultures. While Western critics may point out the rise of visible gay and lesbian movements in parts of the Middle East and Asia, the notion that for Muslims "gay identity" does not exist outside of Western culture was recently supported by Minwalla, Rosser, Feldman, and Varga's (2005) study of Muslims in North America, and by Boellstorff's (2005) study of Indonesian Muslims. However, the Muslim who is homosexual, lives in a Western society and by self-identifying as "gay" may come to experience a similar identity conflict between their sexual orientation and their religious beliefs as experiences by many of his or her Western Christian or Jewish brethren (Minwalla et.…”
Section: Focus On Western Religious Experiencementioning
confidence: 99%
“…The issue of "inconsistency" and skepticism is thus relevant for the investigation of religion and its intersections-among other things, with gender, sexuality, race, as well as institutions such as law and economics-each of which contain a diverse range of concerns and contradictions as they pertain to religion. This presents methodological concerns regarding how persons embody, negotiate, and navigate contradictions, inconsistencies and various forms of bias in religious contexts [46][47][48][49][50][51][52][53]. 2 Kirsch [23], based on fieldwork that emphasized practicality and efficacy, suggested that we substitute belief (conceived as a stable interior state) for believing to denote a state of becoming in the internalization process.…”
Section: Believing Selves and (In)consistencymentioning
confidence: 99%